The Effect of Monetary Economic Variables on Unemployment in Indonesia: Inflation as a Moderating Variable - Solihah, Amilatus (Contemporary Studies in Economic, Finance and Banking, 2025)
Indonesia's primary concern is its high unemployment rate. High unemployment is not only a social issue but also a challenge for the economy, particularly in maintaining inflation stability. The relationship between unemployment and inflation is explained through the Phillips Curve theory. Inflation control can be managed through monetary policy, making this study essential in analyzing the influence of various monetary variables on Indonesia’s unemployment rate, with inflation as a moderating variable. This study examined data collected on a semi-annual basis from 2008 to 2023. The model used in this research followed a recursive simultaneous equation system, applying the Two-Stage Least Squares (2SLS) method. The hypothesis testing results indicated that monetary economic variables did not have a significant effect on unemployment, either directly or through inflation. Additionally, inflation did not significantly impact unemployment. However, interest rates significantly influenced unemployment, aligning with the IS-LM theory. Meanwhile, exchange rates and money supply did not have a significant effect on the unemployment rate.